Research of Computational Intelligence Logistics Distribution Management System Based on Internet - Ge, Zhen; Zhang, Zhe; Zhang, Jian Hua (Applied Mechanics and Materials, 2013)
Since 2010 our research team in-depth study on the subject "Computational intelligence logistics distribution management System". This is the interdisciplinary research, involving computer science, intelligent technology, logistics engineering and management. The research content involves the basic theories of logistics and distribution of intelligence, and the related algorithms and calculation method. In the past three years, we have made gratifying achievements. This project, "Research on computational intelligent logistics distribution management system based on INTERNET", the purpose is to build an open platform in order to provide for the past research application. Only in this way, the past study of the Computational Intelligence Logistics Distribution Management System, further to provide to the society, and create greater economic benefit and social benefit, social service.